AN OVERVIEW OF ORGANIC SOLAR CELLS - Gunes, Serap; Sariciftci, Niyazi Serdar (YILDIZ TECHNICAL UNIV, 2007)
The conversion of sunlight into electricity using solar cells has attracted very much attention during the last decades. Solar energy is clean, abundant and renewable. Solar cells found applications in many different fields such as in calculators, solar lamps and even on spacecraft and satellites. Historically, conventional solar cells were built from inorganic materials. The efficiency of such conventional solar cells made from inorganic materials reached up to 24 %. However, very expensive materials and energy intensive processing techniques are required. Recent efforts are put on the research for new fabrication techniques. New ways of manufacturing that can scale to large volumes and low cost are required for solar cell technologies to achive more wide spread application. A broad range of device technologies are currently being developed, including dye-sensitized nanocrystalline solar cells, polymer/fullerene blends, small molecule thin films and hybrid polymer/nanocrystal devices.
Keywords: Organic solar cells; conjugated polymers; polymer/fullerene blends; PHOTOCURRENT ACTION SPECTRA; PHOTOVOLTAIC DEVICES; SEMICONDUCTING POLYMER; CHARGE SEPARATION; NANOSCALE MORPHOLOGY; TRANSPORT; EFFICIENT; LIGHT; PERFORMANCE; CONVERSION; Engineering